The severity of preaddiction criminal behavior among urban, male narcotic addicts and two nonaddicted control groups - Nurco, David N. (Journal of research in crime and delinquency, 1993)
This study compared cross-sectional and longitudinal changes in the severity of criminal behavior from ages 11 through 14 among three groups of urban males: narcotic addicts and two distinctly different control groups. One never-addicted control group (peer controls) were selected from peers who Were associates of the addicts at age 11. A second never-addicted control group (community controls) was drawn from age-11 male residents of the community at large who were not associates of the addicts. Results indicated clear differences in the criminal behavior patterns of the three subject groups, with addicts reporting the greatest, and community controls the least, involvement in crime in early adolescence at all levels of severity. In addition, within the addict sample, involvement in crime at each severity level was inversely related to age at onset of narcotic addiction. Further, the addicts, regardless of age of onset, are distinguished from controls by noteworthy increases in the proportions of subjects involved in crime, especially at the highest severity level. The implications of the findings for future research and early intervention are discussed. [ABSTRACT FROM AUTHOR]